Efforts to Improve Learning Outcomes of Addition and Subtraction of Numbers through the Direct Learning Model (Direct Instruction for Grade III Elementary School Students) - Bilqist Aqila Izdihar; Anashya Meidyana Azzahra; Jihan Fadilah; Aurellia Putri Irawan; Mawardi Mawardi (Indonesian Journal Publisher, 2026)
The many procedural misconceptions in the material of addition and subtraction operations are the main triggers for the low mathematics learning outcomes of children at the elementary school level. To bridge abstract material with the thinking characteristics of low-grade students, this classroom action research (PTK) was applied by implementing the Direct Instruction model. Using the spiral design of Kemmis and McTaggart, this study involved five grade III students as the main subject. Data were collected comprehensively through evaluation tests, class activity observation sheets, and field notes, which were then processed using qualitative and quantitative descriptive analysis techniques. The findings indicate a substantial improvement in students’ learning outcomes, with the mean post-test score increasing from 34.8 in Cycle I to 82.2 in Cycle II. In line with this, the student learning activity index reached 92 and the teacher's teaching performance reached a score of 88, both categorized as